Global motion perception in children with amblyopia as a function of spatial and temporal stimulus parameters. (October 2016) - Meier, Kimberly; Sum, Brian; Giaschi, Deborah
Highlights: Children with amblyopia showed selective deficits for global motion discrimination. Deficits depended on spatio-temporal stimulus parameters used to create motion. Deficits were apparent at small and medium, but not large, spatial offsets. This corresponded to parameters that take longer to mature in typical development. Abstract: Global motion sensitivity in typically developing children depends on the spatial (Δ x ) and temporal (Δ t ) displacement parameters of the motion stimulus. Specifically, sensitivity for small Δ x values matures at a later age, suggesting it may be the most vulnerable to damage by amblyopia. To explore this possibility, we compared motion coherence thresholds of children with amblyopia (7–14 years old) to age-matched controls. Three Δ x values were used with two Δ t values, yielding six conditions covering a range of speeds (0.3–30 deg/s). We predicted children with amblyopia would show normal coherence thresholds for the same parameters on which 5-year-olds previously demonstrated mature performance, and elevated coherence thresholds for parameters on which 5-year-olds demonstrated immaturities. Consistent with this, we found that children with amblyopia showed deficits with amblyopic eye viewing compared to controls for small and medium Δ x values, regardless of Δ t value. The fellow eye showed similar results at the smaller Δ t . These results confirm that global motion perception in children with amblyopia is particularly deficient at the finer spatial scales that typically mature later in development. An additional implication is that carefully designed stimuli that are adequately sensitive must be used to assess global motion function in developmental disorders. Stimulus parameters for which performance matures early in life may not reveal global motion perception deficits.